CHOOSING INCLUSIVE OR SPECIAL SCHOOLS FOR CHILDREN WITH DISABILITY IN INDONESIA: EDUCATIONAL PLACEMENT AND ANALYSIS OF RELATED FACTORS - Widagdo, The Maria Meiwati; Pudjohartono, Maria Fransiska (Sanata Dharma University Yogyakarta, 2023)
Access to education remains a challenge for children with disability. In Indonesia, families can choose to send children with disability to either inclusive or specialized schools. This study aimed to identify the factors associated with the choice of sending children with disability to inclusive or special schools and factors linked to school dropout. Caregivers of children with disability in Java, Indonesia were interviewed to collect data on enrolment in school, sex and age of the children with disability, type of disability, parents’ age and education, and independence of children with disability. The characteristics of children with disability studying in inclusive and special schools were compared. Logistic multivariate linear regression was done to analyze factors related to the choice of school. Data from 281 children with disability were analyzed: 175 (62.3%) of the school-aged children with disability were actively studying at school, with 84.57% studying in inclusive schools and 15.43% in special schools. Children’s age, independence in daily activities, and ability to learn and play are factors that affect parents’ choice of educational placement for children with disability. Children’s age and mothers’ age are variables influencing children with disability to drop out.